Aktivitas Antioksidan Ekstrak Kulit dan Daging Buah Labu Siam (Sechium edule Sw.) Terhadap Radikal Bebas DPPH - Ibrahim, Arsyik; Irwansyah, Irwansyah; Rusman, Arman; Badawi, Satriani; Riki; Rija'i, Hifdzur Rashif; Fadraersada, Jaka (B-Creta Publisher, 2024)
Chayote is a vines type of plant, and usually people known it as a healthy food and its fruit can be cooked as a vegetable soup. Research aim was to find out the activity from rind and fruit flesh extract of chayote (Sechium edule Sw.) as an antioxidant and find out IC50 from rind and fruit flesh extract of chayote S. edule Sw. After peel the rind of chayote fruit, then chayote rind extracted with soxhletation method and chayote fruit flesh with maceration method. Antioxidant activity evaluated by using DPPH method with spectrophotometry, and IC50 count using regresi linier analysis. This research used methanol extract of chayote rind and methanol extract of chayote fruit flesh. Research results showed that chayote rind extract and chayote fruit flesh have some activity as an antioxidant. IC50 for each sample is 422,38 ppm for methanol extract of chayote rind and 1322,62 ppm for methanol extract of chayote fruit flesh.